Lateral Bearing Strength of Azadirachta indica (neem) under Common Wire Nails - Punhani, R. K.; Pruthi, K. S. (Indian Forester, 1990)
Common Wire Nails have been found to be one of the effective fasteners in any structural/joinery work. Determination of nail strength is a pre-requisite for systematic design and construction of nail-jointed timber units. Neem, being a plantation grown timber should gain momentum in utilization to prOvide timber for shelters in rural and semi-urban areas, food and fodder to the needy. Lateral nail strength values of 3.55 mm and 5 mm dia nails for this timber have been reported in this paper for double shear joints. The research data would enable the designers to properly utilize short length small dimensioned stock of timber in design and construction of nailed timber structures bearing light and medium loads.